2016
DOI: 10.1080/09639284.2016.1191269
|View full text |Cite
|
Sign up to set email alerts
|

Differences in students’ reading comprehension of international financial reporting standards: a South African case

Abstract: This study explores differences in students' reading comprehension of International Financial Reporting Standards in a South African financial reporting class with a heterogeneous student cohort. Statistically significant differences were identified for prior academic performance, language of instruction, first language and enrolment in the Thuthuka programme. Where students, in a heterogeneous financial reporting class, require additional interventions to develop their reading comprehension, instructors may n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 63 publications
(96 reference statements)
0
6
0
Order By: Relevance
“…Due to contradictory findings in South Africa, there is inconclusive evidence on the impact of gender on accounting academic performance. Some studies indicate outperformance by males in undergraduate studies (Jansen & De Villiers, 2016), while others report females outperforming males in both undergraduate studies (Carpenter & Kunaka, 2018;Coetzee et al, 2016) and professional exams (Roos, 2009). Yet other studies have found no correlation between gender and academic performance in undergraduate studies (Bokana & Tewari, 2014;Papageorgiou, 2017;Papageorgiou & Halabi, 2014;Steenkamp, 2014) or in professional exams (van Wyk, 2011).…”
Section: Academic and Demographic Factors Affecting Determinants Of Successmentioning
confidence: 99%
“…Due to contradictory findings in South Africa, there is inconclusive evidence on the impact of gender on accounting academic performance. Some studies indicate outperformance by males in undergraduate studies (Jansen & De Villiers, 2016), while others report females outperforming males in both undergraduate studies (Carpenter & Kunaka, 2018;Coetzee et al, 2016) and professional exams (Roos, 2009). Yet other studies have found no correlation between gender and academic performance in undergraduate studies (Bokana & Tewari, 2014;Papageorgiou, 2017;Papageorgiou & Halabi, 2014;Steenkamp, 2014) or in professional exams (van Wyk, 2011).…”
Section: Academic and Demographic Factors Affecting Determinants Of Successmentioning
confidence: 99%
“…Kong (2006) found that international students experience anxiety and self-doubt when reading in English. As a result, students struggle with reading comprehension in an English language setting (Chi, 1997; Tsao, 2004), inferring a need for intervention to help international students develop their reading comprehension (Coetzee et al , 2016). Self-imposed strategies to understand and improve the pronunciation of English vocabulary includes translation texts and dictionaries (Kong, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the students' inability to discern many accounting reports, textbooks and pronouncements has been well established in the literature (e.g. Adelberg, 1982;Bargate, 2012;Coetzee et al, 2016;Drews-Bryan and Schleifer, 1993;Patel and Day, 1996;Shaffer et al, 1993).…”
Section: Introductionmentioning
confidence: 99%